2010
DOI: 10.1002/clc.20709
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS Complex: A Novel Marker of Cardiovascular Disease

Abstract: QRS complex fragmentation, defined as changes in QRS morphology with different RSR' patterns: additional R waves, notched S wave, or > 1R' wave, has recently been linked with various cardiac conditions and even been postulated to be predictive of outcomes in certain pathologies. The current article aims to consolidate the available information about this morphological ECG abnormality and its predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 19 publications
1
56
0
2
Order By: Relevance
“…In previous studies using Gadolinium delayed enhancement on cardiac magnetic resonance imaging to determine myocardial structure, fQRS related to extensive myocardial scar (11,12). Prior studies demonstrated fQRS to be a marker of a prior MI, defined by regional perfusion abnormalities, which has a substantially higher sensitivity and negative predictive value compared to the Q wave (6,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies using Gadolinium delayed enhancement on cardiac magnetic resonance imaging to determine myocardial structure, fQRS related to extensive myocardial scar (11,12). Prior studies demonstrated fQRS to be a marker of a prior MI, defined by regional perfusion abnormalities, which has a substantially higher sensitivity and negative predictive value compared to the Q wave (6,29).…”
Section: Discussionmentioning
confidence: 99%
“…The reason of documented association between fragmented QRS (fQRS) and increased morbidity and mortality, sudden cardiac death and recurrent CVEs were investigated by several studies (4)(5)(6)(7)(8)(9)(10). In these studies, the main causative mechanism of fQRS was cardiac fibrosis (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The RSR' patterns are sub-classified into fQRS complexes and fragmented wide complexes based on QRS duration [4]. A classic fQRS is only a narrow complex with duration less than 120 ms [16].…”
Section: Fragmented Qrs Vs F-w-qrs Complexesmentioning
confidence: 99%
“…As this new parameter (fragmented QRS [fQRS]) is an easily evaluated ECG sign, it has attracted much attention as a potentially diagnostic and/or prognostic tool for myocardial scar identification in recent years. This novel marker includes various RSR' patterns, and based on the complex duration has been sub classified into two major groups: fQRS complex (< 120 ms duration) and fragmented wide complex (f-wQRS) [4]. Fragmented QRS as defined by Das et al [5] includes only the narrow complexes with the presence of initial R wave followed by an S wave and a terminal positive deflection (R') on a resting 12-lead ECG.…”
Section: Introductionmentioning
confidence: 99%
“…У пациентов с некоронарогенными заболе-ваниями миокарда (миокардиты, аритмогенная кар-диомиопатия/дисплазия правого желудочка (АК/ ДПЖ) и др.) миокардиальный фиброз также может приводить к замедленной и негомогенной деполяри-зации, что проявляется на ЭКГ в виде fQRS [1].…”
unclassified